2018
DOI: 10.1038/s41593-018-0132-2
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Thalamic projections sustain prefrontal activity during working memory maintenance

Abstract: In the version of this article initially published, the title of ref. 45 was given as "Sustaining cortical representations by a content-free thalamic amplifier." The correct title is "Thalamic amplification of cortical connectivity sustains attentional control." The error has been corrected in the HTML and PDF versions of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The MD thalamic nucleus was mostly represented by the CEN, sharing some clusters with the SAL. This seems to be a reasonable representation considering the major anatomical projections to the prefrontal cortex and orbitofrontal cortex and accounting for the functional associations with various cognitive functions, including working memory and executive function 13 , 14 , 16 , 20 , 65 . In addition, the DAN was only reflected in the pulvinar region.…”
Section: Discussionmentioning
confidence: 99%
“…The MD thalamic nucleus was mostly represented by the CEN, sharing some clusters with the SAL. This seems to be a reasonable representation considering the major anatomical projections to the prefrontal cortex and orbitofrontal cortex and accounting for the functional associations with various cognitive functions, including working memory and executive function 13 , 14 , 16 , 20 , 65 . In addition, the DAN was only reflected in the pulvinar region.…”
Section: Discussionmentioning
confidence: 99%
“…However, hippocampal CA3 receives glutamatergic projections mainly from the DG. Moreover, thalamic projections sustain activity of the prefrontal cortex during working memory maintenance [94], and the basolateral amygdala and mPFC forming strong reciprocal synaptic connections support acquisition and extinction of emotional memories [95]. To explore whether the neuroprotective effects of TGR5 are associated with neural circuits of CA3 and mPFC, we selectively blocked the glutamatergic and GABAergic projections using antagonists CPP, NBQX, and gabazine and showed that activation of TGR5 stimulated excitatory pyramidal neuron firing in the hippocampal CA3 and mPFC not due to postsynaptic response.…”
Section: Discussionmentioning
confidence: 99%
“…As a higher order thalamic relay nucleus, the MD is involved in the regulation of the cortico-thalamo-cortical circuit, which means that it can integrate information from the hypothalamus, basal ganglia, olfactory system, amygdala, and cortex, and finally feed back to the cortex (26,27). It is highly correlated with learning, memory, attention, execution, cognition and emotion (13,17,24,28). Therefore, changes in MD neuronal activity may affect the function of normal cortico-thalamocortical circuits and may play an important role in the occurrence of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Previous anatomical evidence has demonstrated interconnections between the MD and the orbitofrontal cortex (OFC), medial prefrontal cortex (mPFC), and granular insular cortex (23)(24)(25). While the mPFC is a brain region that is highly correlated with mood, to observe whether the MD-mPFC pathway is related to depression, we first observed the relationship between the mPFC and depression-like behavior.…”
Section: Increased Excitability Of Mpfc Glu Neurons In Depression-lik...mentioning
confidence: 99%